2021
DOI: 10.3390/ijms22115701
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Organ Crosstalk in Phosphate Homeostasis: Time to Put Phosphate Sensing Back in the Limelight

Abstract: Phosphate homeostasis is essential for health and is achieved via interaction between the bone, kidney, small intestine, and parathyroid glands and via intricate processes involving phosphate transporters, phosphate sensors, and circulating hormones. Numerous genetic and acquired disorders are associated with disruption in these processes and can lead to significant morbidity and mortality. The role of the kidney in phosphate homeostasis is well known, although it is recognized that the cellular mechanisms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Tsoumpra et al [8] showed that high phosphate reduces FGF23-inactivating cleavage in bone, and that this effect is mediated through the FGF receptor FGFR1c. These studies nominate PiT2 and FGFR1c as potential phosphate sensors in bone, upstream of FGF23 [9]. More work is required to understand underlying molecular mechanisms, and to characterize the contribution of these potential sensors to systemic mineral metabolism in health and disease.…”
Section: System-level Phosphate Sensingmentioning
confidence: 99%
“…Tsoumpra et al [8] showed that high phosphate reduces FGF23-inactivating cleavage in bone, and that this effect is mediated through the FGF receptor FGFR1c. These studies nominate PiT2 and FGFR1c as potential phosphate sensors in bone, upstream of FGF23 [9]. More work is required to understand underlying molecular mechanisms, and to characterize the contribution of these potential sensors to systemic mineral metabolism in health and disease.…”
Section: System-level Phosphate Sensingmentioning
confidence: 99%
“…In its organic form, it is a main constituent of cell membranes and essential molecules for energy and intracellular dynamics such as adenosine triphosphate (ATP), nicotinamide adenine dinucleotide (NAD), or cyclic adenosine monophosphate (cAMP). In its inorganic form, it is part of mineralized bone tissue, integrating into hydroxyapatite crystals (Ca 10 (PO 4)6 (OH) 2 ), and participates in the regulation of biomineralization, either through phosphorylated proteins, such as osteopontin and DMP1 (dentin matrix acidic phosphoprotein one), or acting as a signal molecule in the induction of apoptosis in hypertrophic chondrocytes, an essential step for the correct shaping of the end plate during the endochondral ossification process [ 7 ].…”
Section: Phosphate As a Key Element Of Bone Mineralizationmentioning
confidence: 99%
“…In addition, Pi is now recognized as a signaling molecule ( Khoshniat et al, 2011 ; Chande and Bergwitz, 2018 ; Michigami et al, 2018 ; Abbasian et al, 2020a ; Kritmetapak and Kumar, 2021 ). As expected for a metabolite of such central importance, plasma [Pi] is normally regulated within the relatively narrow range of 0.8–1.5 mM in adult humans by the combined actions of the kidney, intestine, bone, and parathyroid gland ( Bergwitz and Jüppner, 2010 ; Komaba and Fukagawa, 2016 ; Beck and Beck-Cormier, 2020 ; Sun et al, 2020 ; Figueres et al, 2021 ). Less is known about intracellular Pi ([Pi] In ) regulation in mammals.…”
Section: Introductionmentioning
confidence: 98%